Suppression of flame propagation in a long duct by inertia isolation with inert gases. (May 2019) - Yang, Hui-Ning; Lin, Yu-Jhen; Liu, Chien-Ho; Chin, Mo-Geng; Wang, Cheng-Chieh; Tsai, Hsiao-Yun; Chen, Jenq-Renn
Abstract: Experimental studies were done with a small pipe with a diameter of 0.043 m and a large pipe with a diameter of 0.49 m to demonstrate the flame propagation suppression with inertia isolation in a long duct. Tests were carried in an ignition section containing propylene/air mixture near stoichiometric concentration and generating a peak flame propagation speed of approximately 100 m/s. The ignition section is connected to a section filled with an inert gas, another section with flammable mixtures, and finally a sufficiently long, ambient section to accommodate flame propagation. The critical length of the inert gas section required for successful suppression of flame from the igniting the flammable section is found to be 0.6 m for CO2 and 0.9 m for N2 in the large pipe and 0.2 m for CO2 and 0.3 m for N2 in the small pipe. Additional tests with a 3 m of ignition section and peak flame propagation speed of 225 m/s showed that the critical length for successful suppression by CO2 is only increased slightly to 0.9 m, confirming that the suppression is a result of inertia isolation rather than inert gas dilution. Finally, application of the results in responding to large-scale leak into a long, underground duct is discussed. Highlights: Suppression the flame propagation in a long duct by inert gas segregation and inertia isolation is proposed. A small pipe with a diameter of 0.043 m and a large pipe with a diameter of 0.49 m were used. Each pipe comprised of an ignition section, an inert gas section, another flammable section, and an ambient section. Critical length of inert gas section required for successful suppression of igniting the flammable section was determined. Application of the results in responding to a large-scale leak into a long duct is discussed.